2014
DOI: 10.1080/13639080.2014.907487
|View full text |Cite
|
Sign up to set email alerts
|

Greening steel work: Varieties of Capitalism and the ‘greening’ of skills

Abstract: Greening steel work: Varieties of Capitalism and the 'greening' of skills

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Thus, employees in the firms that are equipped with sound environmental knowledge through environmental trainings and awareness support the formulation of environmental strategies. This is in line with Evans and Stroud (2016) On the other hand, our results on the impact of consumers on environmental strategy and EI are in line with most contributions (Aragón-Correa & Sharma, 2003;Carballo-Penela & Castromán-Diz, 2015), although in contrast to Buysse and Verbeke (2003). Greater environmental awareness by the consumers directly and indirectly forces firms to carefully structure their environmental strategy in order to retain their market share.…”
Section: Eb2 Foreign Buyers Environmental Regulation Influences Businsupporting
confidence: 87%
See 2 more Smart Citations
“…Thus, employees in the firms that are equipped with sound environmental knowledge through environmental trainings and awareness support the formulation of environmental strategies. This is in line with Evans and Stroud (2016) On the other hand, our results on the impact of consumers on environmental strategy and EI are in line with most contributions (Aragón-Correa & Sharma, 2003;Carballo-Penela & Castromán-Diz, 2015), although in contrast to Buysse and Verbeke (2003). Greater environmental awareness by the consumers directly and indirectly forces firms to carefully structure their environmental strategy in order to retain their market share.…”
Section: Eb2 Foreign Buyers Environmental Regulation Influences Businsupporting
confidence: 87%
“…These databases were mainly used to develop training modules for employees (Evans & Stroud, 2016) and to inform employees about the current environmental issues around the globe. Therefore, emphasis was only given to consumer pressure.…”
Section: Financial Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of refuse processing found only 16 per cent of workers receiving training (CEDEFOP, : 87) and even that mostly unregulated, on‐the‐job, typically between a few hours and a few days ( ibid . : 57; Evans and Stroud, ). Gregson et al .…”
Section: The Dirty Jobs Of E‐waste Managementmentioning
confidence: 99%
“…Policy and legislation have helped create work through the requirement of certain services and products and been the main driver for certain segments of the green economy, rather than self‐sustaining market mechanisms (Pearce and Stilwell, ). For example in the UK recent environmental policies have been closely linked to the expansion of apprenticeship places and the development of new qualifications for the ‘low‐carbon economy’ (CEDEFOP, : 32; Evans and Stroud, ).…”
Section: The Promised Jobs Of the Green Economymentioning
confidence: 99%